Pengaruh Lama Kontak Albumin terhadap Remineralisasi Lesi Karies Dini - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2004)
The progression of early caries lesions depends on demineralization and remineralization process. Remineralization can repair damage that is caused by demineralization before cavitation, The purpose of this study was know the influence of albumin contact duration on calcium and phosphate concentration in enamel as remineralization indicator of early caries lesion. In the study, twenty maxillary bicuspids with early caries lesion simulation with made by demineralization in vitro on proximal surfaces were used. After deproteination, the teeth were divided into 4 groups. Group I as a control group, the teeth were immersed in aquadest. Group II teeth were immersed in albumin solution of 1 ring/m1 for 5 hours. The teeth in group III and IV were immersed in albumin solution of 1 mg/ml for 10 hours and 15 hours. After all, the teeth were rernineralized in vitro with remineralization solution that contained CaCl2 of 1.5 mM, KH2PO4 0.9 mM and NaF 1 ppm for 4 weeks at 370 C. Measurement of the calcium and phosphate concentrations were carried out with Atomic Absorbance Spectroscopy and Spectrophotometry on tooth specimen solution which was taken from mesial and distal surfaces. Data of this study were statictically analyzed with one way ANOVA. The result of this study showed that there was significant difference (p0